PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP HASIL BELAJAR IPS PADA MATERI PERKEMBANGAN TEKNOLOGI TRANSPORTASI DI KELAS IV SD NEGERI 101800 DELI TUA - ULFAH SARI REZEKY; TINA SHEBA CORNELIA (JURNAL ILMIAH MAKSITEK, 2020)
This research seeks to find problem solving in IPS in class IV in elementary school, especially the influence of image media in the learning results of IPS subjects on the development of transportation technology. The goal to be achieved is to improve students ' learning outcomes by using image media on the materials of the development of transportation technology. This research will be conducted in in Grade IV Elementary school 101800 old Deli. The population is a class IV student consisting of 2 classes. With the number of students in the Ekperimen class 27 students, and in the control class 24 students. This research is a quasi-experimental research (pseudo-experimentation) aimed at knowing there is a consequence of an imposed subject of students. In accordance with the research above the design used in this research is, Pretest-Postest Control Group design. One group of experiments was given treatment with the learning of image media, while the control group was given conventional learning treatment. The experiment class is given the image media treatment.While in the control class with conventional learning. Preliminary tests (pretests) were conducted prior to treatment of the classes studied, while the final Test (Posttest) was conducted after treatment of initial test (pretest). The targeted external research on this study is the result of a study published on an unaccredited National Journal that will be published at Quality University.